Study of Student Self-Efficacy in Online Learning in the Era of the Covid-19 Pandemic - Rosali, Ely Satiyasih; Ningsih, Mega Prani; Darmawan, Darwis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
The purpose of this study was to examine student self-efficacy in online learning in the era of the Covid-19 pandemic. This research is a quantitative research through survey method. The population and sample are students majoring in Geography Education, FKIP, Unsil class 2018, 2019, and 2020 with a total of 200 students. Data collection is distributed through google form. The research instrument used a Likert scale which was distributed in each answer to the questions in the questionnaire. Data analysis used quantitative descriptive analysis with percentages. The results of the study on the self-efficacy scale, namely 63.5% moderate level, 29.5% low level and 7% high level. Analysis of student self-efficacy is studied based on the dimensions of self-efficacy, namely the magnitude dimension shows students have a high enough level of optimism in conducting lectures and completing tasks given by the lecturer in charge of the course, the strength dimension shows students believe and know the advantages that exist within them so that they are able to carry out all activities in lectures as a form of development and hone their potential, the generality dimension shows students have the ability to solve their problems but some problems may need the help of others in solving them. Students’ self-efficacy in conducting Distance Learning during the covid pandemic is on average still in the moderate category. This means that students already have sufficient self-efficacy but still need to get supportive motivation.